Unintentional injuries in the rural population of Twiserkan, Iran: A cross-sectional study on their incidence, characteristics and preventability - Naghavi Mohsen; Rezapur-Shahkolai Forouzan; Shokouhi Mohammadreza; Laflamme Lucie (BMC, 2008)
Abstract Background Knowledge is sparse concerning injuries affecting rural populations in low and middle-income countries in general and in Iran in particular. This study documents the incidence and characteristics of severe injuries affecting rural people in the Iranian district of Twiserkan and it investigates these people's suggestions for injury prevention and control. Methods An interview-based investigation was undertaken that comprised all unintentional injuries leading to hospitalization (more than 6 hours) or death that had occurred within a twelve month period and that were identified in the files of the 62 "health houses" of the Twiserkan district. For each case, semi-structured interviews were conducted at the households of the injured people (134 injuries affecting 117 households were identified). Results The incidence rates of fatal and non-fatal injuries were respectively 4.1 and 17.2 per 10 000 person-years and, as expected, men were more affected than women (77.6% of all injury cases). Traffic injuries (in particular among motorcyclists) were as common as home-related injuries but they were far more fatal. Among common suggestions for prevention, people mentioned that the authorities could work on the design and engineering of the infrastructure in and around the village, that the rural health workers could contribute more with local information and education and that the people themselves could consider behaving in a safer manner. Conclusion Not only domestic injuries but also those in traffic are an important cause of severe and fatal injury among rural people. Health workers may play an important role in injury surveillance and in identifying context-relevant means of prevention that they or other actors may then implement.